(untitled) (World Bulletin of Management and Law, 2025)
This article reveals the organization, structure, goals and tasks of the Committee on the Elimination of Discrimination against Women (CEDAW). Also, the Charter of the Committee, the provisions of the Convention on the Elimination of All Forms of Discrimination against Women are included